Current Treatment of Cleft Lip and Palate - Gülşen, Ayşe (IntechOpen, 2020)
Non-syndromic cleft lip and palate patients have the most common congenital anomalies that affect the middle and lower part of the face, and which impair aesthetic integrity. These anomalies also affect basic functions such as hearing, speaking, chewing, and breathing. Treatment of patients with cleft lip and palate requires multidisciplinary teamwork. The cleft child should be followed and treated by a team of experts from different disciplines who work well together. Although cleft surgery, orthodontic treatment, and speech therapy are the main disciplines, each of the other branches (maxilla-facial-surgeon, otolaryngologist, speech therapist, pediatric dentist, psychologist, nurse etc.) are also very important. In this book, we wanted to present the reader with the experiences and knowledge of some of these disciplines. This book also includes information on the quality of life of children with this anomaly and anesthesia evaluation, which is very important for the cleft surgery.